Be my Guest! From Welcome to Hospitality in Libraries - Bats, Raphaëlle (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2025)
Although inclusion and welcoming have been at the heart of French librarians' concerns for many years, the actions undertaken seem to have reached their limits. The participation of participants remains the business of informed people, the inclusion of minorities does not go as far as rethinking the modes of cultural transmission, and the ways to listen to the inhabitants are often restricted to design thinking. And if the current approach to welcoming ideas, stories and people was not sufficient to meet our expectations for inclusion and diversity? Through a theoretical study of concepts and notions, we study the relevance of the idea of hospitality, and its duality (hospitality to those who are in needs and to the foreigners) to renew the approach of welcoming in libraries. Our paper tends to show the paths that this notion opens up in terms of knowledge legitimization, community literacy and documentary hospitality. Thus, we hope to better identify the critical factors of inclusive library policies and subsequently propose directions for the renewal of welcoming practices in libraries.